Purchase intention of smarthome products in milennial generation - Bun Norikun (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research examines purchase intentions with the supporting factors of online reviews, price, perceived product quality, and emotional value of smarthome products on online platforms. The sample for this research consisted of Kudus City, Jepara, Pati, Rembang, Semarang, Yogyakarta and Jakarta with 107 respondents. The analysis used is Structural Equation Modeling (SEM). The conclusions that can be drawn from this research are that online reviews have a significant effect on perception of product quality and price, online reviews have no significant effect on purchase intention and emotional value, price has a significant effect on perception of product quality, price has no significant effect on purchase intention and emotional value, Perception of product quality has a significant effect on emotional value, Perception of product quality has no significant effect on purchase intention, Emotional value has a significant effect on purchase intention.